2014
DOI: 10.1590/s1517-83822014000300037
|View full text |Cite
|
Sign up to set email alerts
|

Lack of AHL-based quorum sensing in Pseudomonas fluorescens isolated from milk

Abstract: Numerous bacteria coordinate gene expression in response to small signalling molecules in many cases known as acylhomoserine lactones (AHLs), which accumulate as a function of cell density in a process known as quorum sensing. This work aimed to determine if phenotypes that are important to define microbial activity in foods such as biofilm formation, swarming motility and proteolytic activity of two Pseudomonas fluorescens strains, isolated from refrigerated raw milk, are influenced by AHL molecules. The test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…As described by Martins et al . [64], quorum sensing systems based on N-acyl-homoserine lactone (AHL) signalling molecules have been identified in a few P . fluorescens strains [37,6568].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Martins et al . [64], quorum sensing systems based on N-acyl-homoserine lactone (AHL) signalling molecules have been identified in a few P . fluorescens strains [37,6568].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that other strains of P . fluorescens do not produce AHLs [64,69,70]. Standalone blast analyses of the MFE01 draft genome indicated that it did not contain any genes encoding a protein corresponding to the conserved AHL synthase (WP_044464955.1).…”
Section: Resultsmentioning
confidence: 99%
“…Through the quorum sensing system bacteria are capable of performing tasks as a group such as migration to more favorable environments, biofilm formation, virulence gene expression, bacteriocin and antibiotic production, bioluminescence, pigment production, among others (Martins et al, 2014;Skandamis & Nychas, 2012). The system has also been shown to regulate bacterial behaviors in food ecosystems highlighting the importance of understanding its control in order to improve food safety and quality (Bai & Rai, 2011;Pinto et al, 2007;Skandamis & Nychas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…() and Martins et al. () both found that two highly proteolytic P. fluorescens strains (07A and 041), which were isolated from raw milk, did not produce AHL molecules in any of the tested media. In addition, synthetic AHLs added to the medium did not influence the production of proteases (Pinto et al., ).…”
Section: Biological Properties Of Protease Aprxmentioning
confidence: 95%
“…Juhas, Eberl, and Tümmler (2005), and Liu, Wang, and Griffiths (2007) reported that quorum sensing systems are widespread among pseudomonads. However, Pinto et al (2010) and Martins et al (2014) both found that two highly proteolytic P. fluorescens strains (07A and 041), which were isolated from raw milk, did not produce AHL molecules in any of the tested media. In addition, synthetic AHLs added to the medium did not influence the production of proteases (Pinto et al, 2010).…”
Section: Regulation Of Aprx Productionmentioning
confidence: 98%